Ternary Aluminides of a New Homologous Series—CePt2Al2 and CePt3Al3: Crystal Structures and Thermal Properties - Elena Murashova; Yuliya Morozova; Sergey Dunaev; Zhanafiya Kurenbaeva; Anna Tursina (Crystals, 2020)
In the process of studying the Ce–Pt–Al system, we identified CePt2Al2 and CePt3Al3, two new ternary intermetallic compounds. CePt2Al2 aluminide undergoes a structural phase transition from a low-temperature orthorhombic modification (of its own structure type, Cmme, a = 5.84138(2) Å, b = 6.39099(3) Å, c = 10.11611(5) Å) to a high-temperature tetragonal modification (CaBe2Ge2 type, P4/nmm, a = 4.3637(9) Å, c = 10.0925(14) Å) at 280(1) °C. CePt3Al3 crystallizes with a new type of structure (Cmme, a = 6.36548(6) Å, b = 5.78301(6) Å, c = 13.36245(19) Å) built of structural units of low-temperature orthorhombic CePt2Al2-type and CsCl-type.